Behavioural and patient-individual determinants of quality of life, functioning and physical activity in older adults (MobilE-TRA 2): study protocol of an observational cohort study in a tertiary care setting - Daniela Koller; Eva Grill; Lars Schwettmann; Benedict Katzenberger; Martin Weigl; Alexander Paulus; Sara Pedron; Sebastian Fuchs (BMJ Open)
Introduction Vertigo, dizziness and balance problems (VDB) as well as osteoarthritis (OA) are among the health conditions with the greatest impact on mobility and social participation in older adults. Patients with VDB and OA were shown to benefit from specialised care such as vestibular rehabilitation therapy or joint replacement. However, these effects are not permanent and seem to disappear over time. One important reason might be a decreasing adherence to therapy recommendations. Findings from behavioural economics (BE) can help to shed light on individual effects on adherence behaviour and long-term outcomes of VDB and OA.Objective Based on insights from BE concepts (ie, self-efficacy, intention, and time and risk preferences), MobilE-TRA 2 investigates the determinants of functioning and health-related quality of life (HRQoL) 3 and 12 months after discharge from total hip replacement (THR)/total knee replacement (TKR) in patients with OA and after interdisciplinary evaluation for VDB.Methods and analysis MobilE-TRA 2 is a longitudinal observational study with data collection in two specialised tertiary care centres at the university hospital in Munich, Germany between 2020 and 2023. Patients aged 60 and older presenting for their first THR/TKR or interdisciplinary evaluation of VDB at Ludwig Maximilians University (LMU) hospital will be recruited for study participation. Three and twelve months after baseline assessment, all patients will receive a follow-up questionnaire. Mixed-effect regression models will be used to examine BE concepts as determinants of adherence, HRQoL and functioning.Ethics and dissemination The study was approved by the ethics committee at the medical faculty of the LMU Munich under the number 20-727. Results will be published in scientific, peer-reviewed journals and at national and international conferences. Findings will also be disseminated via newsletters, the project website and a regional conference for representatives of local and national authorities.